3D-Printed Hydrogel Scaffolds Loaded with Flavanone@ZIF-8 Nanoparticles for Promoting Bacteria-Infected Wound Healing - Jian Yu; Xin Huang; Fangying Wu; Shasha Feng; Rui Cheng; Jieyan Xu; Tingting Cui; Jun Li (Gels)
Bacterial-infected skin wounds caused by trauma remain a significant challenge in modern medicine. Clinically, there is a growing demand for wound dressings with exceptional antibacterial activity and robust regenerative properties. To address the need, this study proposes a novel multifunctional dressing designed to combine efficient gas exchange, effective microbial barriers, and precise drug delivery capabilities, thereby promoting cell proliferation and accelerating wound healing. This work reports the development of a 3D-printed hydrogel scaffold incorporating flavanone (FLA)-loaded ZIF-8 nanoparticles (FLA@ZIF-8 NPs) within a composite matrix of κ-carrageenan (KC) and konjac glucomannan (KGM). The scaffold forms a stable dual-network structure through the chelation of KC with potassium ions and intermolecular hydrogen bonding between KC and KGM. This dual-network structure not only enhances the mechanical stability of the scaffold but also improves its adaptability to complex wound environments. In mildly acidic wound conditions, FLA@ZIF-8 NPs release Zn2+ and flavanone in a controlled manner, providing sustained antibacterial effects and promoting wound healing. In vivo studies using a rat full-thickness infected wound model demonstrated that the FLA@ZIF-8/KC@KGM hydrogel scaffold significantly accelerated wound healing, showcasing its superior performance in the treatment of infected wounds.